Elemen Tazkiyah al-Nafs dalam gagasan negara zikir Brunei Darussalam: Kajian terhadap amalan kerohanian sebagai asas pembangunan kerohanian golongan Belia Perlu Perhatian (BPP) / Masuriyati Yahya - Masuriyati , Yahya (2017)
The youths are the leaders of today's generation and as backup for future leaders. They are an important subject in the development plan of a country. This coincided with the idea of National Remembrance of Brunei Darussalam to build an excellent personalities of youths through spiritual practice as a spiritual method that youths always remember and obey Allah the Almighty. The Youths Need Attention who became a focus of this study are in need of restoration and spiritual guidance that emphasizes spiritual practice as an element of tazkiyah al-nafs to form a righteous man, faithful and devoted. This study aimed to examine the concept of tazkiyah al-nafs, the idea of National Remembrance of Brunei Darussalam, the modes of programs in strengthening the idea of National Remembrance through spiritual practices towards Youths Need Attention, especially the zikrullah practices as a method of tazkiyah al-nafs. This study applied the conventional design that combines qualitative methods (library and ethnographic) as well as quantitative method (survey questionnaire). The samples were randomly selected from the group of Youths Need Attention. Type of this research is a correlation study and analyzed using software the Statistical Package for the Social Science (SPSS). The analysis showed that the mean scores for each component of the spiritual practices that form the basis of spiritual programs and activities of the Youths Need Attention in low level. While the level of strength of the relationship between all components of spiritual practices analyzed through the Test of Correlation Coefficient (r) indicating the imbalance in the components of spiritual practices. This study proved that the existing spiritual programs and activities in the strengthening programs of the idea of National Remembrance through spiritual practices towards the Youths Needs Attention particularly the zikrullah practices as a method of tazkiyah al-nafs unable to enhance the spiritual development of the samples, particularly in terms of enhancing self-control internally and it is also less effective in changing the characters of those youths’ to the maximum level. Thus, the study suggested improvement to be referred by the initiators, administrators and compilers of the spiritual programs and activities who are involved in strengthening the idea of National Remembrance in improving the existing spiritual programs and activities by intensifying the elements of tazkiyah al-nafs especially the practices of zikrullah. It is important that all spiritual programs and activities conducted pursuant and in line with the objectives of the idea of National Remembrance of Brunei Darussalam.